Pengaruh Penggunaan Model Think Talk Write Terhadap Kemampuan Menulis Teks Pidato Pada Siswa Kelas IX SMP Negeri 17 Padang - Putri, Devia Dwi Putri; Afdetis Mana, Lira Hayu; Pebriani, Yulia (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2023)
The purpose of this study is to describe how the influence of the use of the Think Talk Write model has on the skills of writing speech texts in Class IX students of SMP Negeri 17 Padang. This type of research is quantitative research. The method used in this study is the pre-experimental method. The population in this study were class IX students of SMP Negeri 17 Padang who were enrolled in 2022-2023, while the sample for this study was class IXB with a total of 26 students. The X variable is the Think Talk Write model, while the Y variable is the ability to write speech texts. The research instrument used was the test. The data collection technique used in this study was to provide performance tests. The tests were given twice in the form of pretest and posttest. At the first meeting the teacher conducted teaching and learning activities. In the second meeting the teacher carried out teaching and learning activities using the Think Talk Write model. At the third meeting the teacher gave a posttest. The results of this study are that H1 is accepted and H0 is rejected. Thus the use of the Think Talk Write model influences the speech writing skills of class IX students of SMP Negeri 17 Padang.